2012
DOI: 10.1079/9781780641010.0000
|View full text |Cite
|
Sign up to set email alerts
|

Camel meat and meat products

Abstract: This book, composed of 14 chapters, aims to provide basic information which contributes to the understanding of camel meat production. Topics discussed include camel taxonomy, history and worldwide distribution; camel nutrition and growth; slaughtering and processing; carcass and meat yield and quality; nutritive value of the meat; interventions for the improvement of meat quality; and the economic potential of camel meat. This book is intended as a foundation text with an emphasis on general principles and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(1 citation statement)
references
References 172 publications
0
1
0
Order By: Relevance
“…Azizollah et al [10] identified different genera of bacteria from samples collected before and after slaughter from the respiratory system of healthy camels in an abattoir in Iran. Other countries where the normal respiratory bacteria of camels have been studied include Nigeria [11], Ethiopia [12], and Somalia (Mogadishu) [13]. Despite these observations, studies on bacterial flora of apparently healthy camels are rare globally [5] with none reported in Kenya, although pastoralists in Kenya report high incidences of camel respiratory diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Azizollah et al [10] identified different genera of bacteria from samples collected before and after slaughter from the respiratory system of healthy camels in an abattoir in Iran. Other countries where the normal respiratory bacteria of camels have been studied include Nigeria [11], Ethiopia [12], and Somalia (Mogadishu) [13]. Despite these observations, studies on bacterial flora of apparently healthy camels are rare globally [5] with none reported in Kenya, although pastoralists in Kenya report high incidences of camel respiratory diseases.…”
Section: Introductionmentioning
confidence: 99%